GLANDULAR ODONTOGENIC CYST OF THE MAXILLA: A UNIQUE PRESENTATION OF AN UNCOMMON ENTITY (Bangladesh Journal of Medical Science, 2026)
Glandular odontogenic cyst (GOC) is a rare developmental odontogenic cyst of the jaws that usually presents as a slowgrowing asymptomatic swelling, but it is locally aggressive and shows a tendency for recurrence. Clinico-radiographically, GOC can mimic numerous odontogenic cysts and tumors, making preoperative diagnosis challenging. Radiographically, it commonly appears as a well-defined unilocular or multilocular radiolucency with scalloped margins. Histopathology is characteristic but may still be confusing because the lining shows glandular features with mucin-producing goblet cells, which may suggest salivary gland origin or lead to misdiagnosis as mucoepidermoid carcinoma. However, absence of salivary gland markers and the presence of odontogenic epithelial features support its odontogenic lineage. Presentation in the maxilla is distinctly uncommon. We report a case of GOC with a rare maxillary presentation in a 34-year-old female patient, highlighting the clinical, radiographic, and histopathological diagnostic challenges and the importance of accurate diagnosis for comprehensive treatment planning and reduction of recurrence risk.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S355-S358